Pengaruh Media Kapija terhadap Kemampuan Membaca Kata Beraksara Jawa Siswa Kelas 3 Madrasah Ibtidaiyah - Nasihah, Ati Dinan; Prabowo, Dimas Setiaji; Hidayat, Mohamad Wahyu (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
This research aims to analyze and explore the influence of using KAPIJA (Javanese Smart Card) media on the ability to read Javanese words in grade 3 students at MI Miftahul Ulum Kalitorong. The research method used was a quantitative type of experiment with a one group pretest-posttest design with the research subjects being all grade 3 students so that sampling used total sampling. Data is collected through documentation and tests. The results of the research show that there are differences in values and influences before and after using KAPIJA (Javanese Smart Card) media on the ability to read Javanese script words. One of the language skills taught in elementary schools is the ability to read. One of the reading skills taught is reading Javanese words. Apart from the quality of human resources to improve the ability to read Javanese script, there is also a need for media that teachers use. Even though the use of KAPIJA media was successful in improving reading skills, research also identified several obstacles in learning Javanese, such as a lack of supporting facilities for learning so that students felt bored. To overcome these obstacles, teachers can utilize the strategies, models and media used in learning and involve students in every learning activity.